BANKING SYSTEM OF UKRAINE: TERRITORIAL STRUCTURE AND CHALLENGES OF THE PRESENTATION - Medynska , T.V.; Bodnaryuk , I.L.; Kropelnytska, S.O. (The actual problems of regional economy development, 2017)
The article analyzes the quantitative indicators characterizing the banking system of Ukraine and its territorial structure. The analytical estimation of the number of banking institutions in Ukraine and the territorial structure of the network of commercial banks, in particular, the definition of the level of provision by the banking institutions of the western region and the identification of certain issues of national security of the country and the stability of the banking system connected with the nationalization of Privatbank, has been carried out. Novelty is to determine the level of security provided by banking institutions in the western region and to identify specific issues of national security of the country and the stability of the banking system. Practical significance is to provide concrete suggestions for improving these processes.